Metabolome-wide associations with short-term exposure to PM2.5-bound polycyclic aromatic hydrocarbons: a study in older adults - Haoneng Hu; Quan Zhou; Kang Cao; Yu Jiang; Jianjun Xiang; Jing Wu; Jin Li; Zhiwei Chen; Shuling Kang; Dandan Zhu; Huaying Lin; Chuancheng Wu (Frontiers in Public Health)
BackgroundEmerging evidence links fine particulate matter (PM2.5) and its polycyclic aromatic hydrocarbon (PAH) components to adverse health outcomes. However, the biological mechanisms driving these associations remain unclear. This study innovatively integrates personal exposure monitoring and untargeted metabolomics in an older adult population to investigate the differential impacts of individual PM2.5-bound PAHs on metabolic pathways and elucidate their roles in health risks.MethodsIn this study, we enlisted the participation of 112 healthy older adults. We employed personal samplers to monitor the concentrations of pollutants throughout the study period. Furthermore, we conducted an untargeted metabolomic analysis of plasma samples using a liquid chromatograph mass spectrometer (LC–MS). A general linear regression model was utilized to investigate the significant relationships between metabolites and pollutants. Metabolic pathway enrichment analysis was performed to reveal the disturbed metabolic pathways related to PM2.5-bound PAHs.ResultsOur study demonstrated that short-term exposure to PM2.5-bound PAHs may induce acute perturbations in plasma metabolites among the older adult population. We found that exposure to LMW PAHs in PM2.5 were correlated with amino acid metabolic pathways, while HMW-PAHs are associated with fatty acid and cholesterol metabolism pathways. While PM2.5 mass was higher in summer, the toxic PAHs component of PM2.5 was substantially higher in winter, contributing to greater observed toxicity.ConclusionThe plasma metabolome presents a promising resource for biomarkers and pathways, elucidating the biological mechanisms of PM2.5-bound PAHs. Our findings suggest that the cholesterol and citric acid metabolites, as well as the cholesterol biosynthesis and citric acid cycle pathways they affect, may play important roles in the health damage caused by PAHs, providing potential insights into the pathogenic processes underlying the impact of PM2.5-bound PAHs.